Chromium Distribution and Spatial Variations in the Finer Sediment Grain Size Fraction and Unfractioned Surficial Sediments on Nyanza Gulf, of Lake Victoria (East Africa). (17th May 2016) - Mwamburi, Job
Abstract : Surficial sediments collected from the Nyanza Gulf of Lake Victoria (East Africa) were used to determine spatial concentrations of Cr and determine differences in contents of the unfractioned (whole sediment) and the finer grain size sediments, establishing any changes in Cr enrichment and potential ecological risks using sediment quality guidelines. A single pollution index was also used to evaluate level of Cr contamination. The spatial mean Cr contents in the <63 µ m (silt-clay) fraction were found to be significantly lower than those in the unfractioned sediments, but with a strong linear positive correlation. The study results show decreasing spatial amounts of Cr in surficial sediments of the Nyanza Gulf, when compared to a study done 20 years earlier. However, the 95% confidence limits of the overall mean Cr in unfractioned sediments exceed the threshold effect concentration (TEC), indicating the potential for Cr remobilization from sediments. In general the sediment enrichment is evidence of possible dominance of lithogenous sources of Cr in the surface lake sediments, with potential anthropogenic sources from the drainage system and nearshore urban areas. The sediments are unpolluted with respect to geoaccumulation index, and sediment enrichment factors suggest a minor to moderate enrichment of Cr in surficial sediments of three sites around the Nyanza Gulf zones and around the river mouth in the main lake.